Traditional kite game as an effort to overcome stress for elementary school students during the covid-19 pandemic - Budiman, Indra Adi; Hendrayana, Yudy; Sofyan, Davi (Jurnal Keolahragaan, 2023)
The purpose of this research is to carry out a traditional game, especially a kite, as an effort to overcome stress in elementary school students during the COVID-19 pandemic. Quantitative research with the type of survey research is carried out in this study. The sample in this study amounted to 10 students. The sample was selected based on being domiciled in a block whose houses were not far apart so that it was easy to condition them. The distribution of questionnaires and performing organized interviews with parents and kids make up the data collection process. In this study, the Lovibond and Lovibond DASS (Depression Anxiety Stress Scale) questionnaire 42 was utilized. Both quantitative and qualitative descriptive methodologies were used to analyze the data. The findings demonstrated that the scores obtained were based on DASS 42 from the circumstances before the test to overcome stress with kite flying and after. Before the trial, the stress value was 31.7, then after that, there was a decrease of around 16.7, which is in the range of 15. Thus, overcoming stress through the traditional kite game is considered quite successful for elementary school students during the COVID-19 pandemic. There are limitations in this study because it is not able to describe the situations of students with a larger scope, different cultures, physical conditions, and urban play environments. Recommendations for further researchers to conduct research for students in overcoming stress against high pressure in the learning process through the form of methods, strategies, and other games.